Comparison of clonidine with bupivaicaine vs plain bupivaicaine in transversus abdominis plane (TAP) block in women undergoing cesarean delivery under spinal anesthesia: Randomized clinical trial - Sunil Thakur; Anupriya Sharma; Sushruti Kaushal; Ashish Sharma; Nisha Sharma; Preyander S Thakur (Wolters Kluwer Medknow Publications, 2023)
Introduction: Transversus abdominis plane (TAP) block is a technique of regional anesthesia, introduced by Rafi in 2001. Various additives have been added to prolong the duration of effect of TAP block. We conducted this study to see if addition of clonidine to bupivacaine significantly increases the duration of effect of TAP block. Materials and Methods: This randomized, parallel group, placebo controlled double blind clinical trial was conducted on 100 healthy participants (ASAII) undergoing LSCS under Spinal anesthesia (SA) from Jan 2021 to July 2021 after consent of Institutional Ethics Committee. Women with contraindications to spinal anesthesia, allergy to any of the drugs or not-suitable for cesarean under SA were excluded. After written informed consent, eligible participants were randomly allocated into two groups using computer generated random number tables using serially numbered opaque sealed envelopes. 48 out of 50 participants in group A (Bupivacaine) were given TAP block with 20 ml of 0.25% bupivacaine bilaterally. 2 women were excluded because of conversion to General Anesthesia. Similarly, 47 out of 50 participants in Group B (Bupivacaine + Clonidine) were given TAP block with 20 ml of 0.25% bupivacaine plus 1.0 mcg/kg clonidine bilaterally after completion of surgery using 18 G Tuohy needle. Separate person used to fill the drugs for block. Participants were assessed for duration of analgesic effect of TAP block measured as the time to request for additional analgesia. Additional analgesic requirement was noted. Participants were assessed for side effects of clonidine like hypotension, bradycardia, sedation and dryness of mouth. Overall patient satisfaction was also noted. Data was analysed using Graphpad Prism 9, using Student's t-test for primary outcome and Mann-Whitney U test for secondary outcomes. Results: The mean 'duration of analgesic effect with TAP block' was 6.34 (SD1.26) hrs for 'Bupivacaine' group and 10.56 (SD2.12) hrs for 'Bupivacaine + Clonidine' group. None of the patients developed hypotension or bradycardia. 25% participants in Bupivacaine only group and 40.42% in Bupivacaine + Clonidine group were sedated (P < 0.05). 20.8% in 'Bupivacaine' group and 51.06% in 'Bupivacaine + Clonidine' group had dryness of mouth (P < 0.001). Patient satisfaction was equal in both the groups. Conclusion: Addition of clonidine to bupivacaine in the dose of 1 mcg/kg significantly increases the duration of analgesic effect of TAP block, decreases analgesic usage without significant increase in side effects.